Single-component organic solar cells—Perspective on the importance of chemical precision in conjugated block copolymers - Theunissen, Dries; Smeets, Sander; Maes, Wouter (Frontiers in Chemistry, 2023)
Organic photovoltaics (OPV) present a promising thin-film solar cell technology with particular benefits in terms of weight, aesthetics, transparency, and cost. However, despite being studied intensively since the mid 90’s, OPV has not entered the mass consumer market yet. Although the efficiency gap with other thin-film photovoltaics has largely been overcome, active layer stability and performance reproducibility issues have not been fully resolved. State-of-the-art OPV devices employ a physical mixture of electron donor and acceptor molecules in a bulk heterojunction active layer. These blends are prone to morphological changes, leading to performance losses over time. On the other hand, in ‘single-component’ organic solar cells, the donor and acceptor constituents are chemically connected within a single material, preventing demixing and thereby enhancing device stability. Novel single-component materials affording reasonably high solar cell efficiencies and improved lifetimes have recently emerged. In particular, the combination of donor and acceptor structures in conjugated block copolymers (CBCs) presents an exciting approach. Nevertheless, the current CBCs are poorly defined from a structural point of view, while synthetic protocols remain unoptimized. More controlled synthesis followed by proper structural analysis of CBCs is, however, essential to develop rational structure-property-device relations and to drive the field forward. In this perspective, we provide a short overview of the state-of-the-art in single-component organic solar cells prepared from CBCs, reflect on their troublesome characterization and the importance of chemical precision in these structures, give some recommendations, and discuss the potential impact of these aspects on the field.